Insight into the mechanism of selective mono-N-methylation of aniline on Cu1-xZnxFe2O4: a DRIFTS study - Vijayaraj, M.; Murugan, B.; Shubhangi B. Umbarkar; Hegde, S. G.; Gopinath, Chinnakonda S. (Journal of Molecular Catalysis A - Chemical, 2005)
Mechanism of selective mono-N-methylation of aniline with methanol on Cu1-xZn2FeO4 catalysts was investigated in detail. The interaction of reactants (aniline. methanol and methanol: aniline) and possible products (N-methylaniline (NMA), N,N-dimethylaniline (DMA) and o-toluidine (OT)) on catalysts surface was studied by temperature-dependent in situ FTIR spectroscopy. Methanol adsorbs dissociatively over catalysts surface at 373 K as methoxy species and is oxidized to formate species at high temperature through dioxymethylene and/or formaldehyde as a surface intermediate species. On the other hand, adsorption of aniline:methanol mixtures shows that methanol oxidation was completely hindered in the presence of aniline. Aniline adsorbs on the Lewis acid sites at <= 373 K with phenyl ring oriented in a perpendicular manner to the catalyst surfaced however, N-H bond scission occurs above 373 K. A comparison of adsorbed NMA and methanol: am line (3:1) mixture on Cu0.5Zn0.5Fe2O4 shows NMA forms from the reaction mixture at 473 K. However, maximum activity at 573 K in catalytic reaction studies suggests that desorption limits the methylation kinetics. FTIR study displays stable aniline and methyl species on ZnFe2O4 even at 573 K; however. no methyl species is detected on Cr0.95Zn0.05Fe2O4 at 473 K due to methanol reforming reaction and that limits the overall reaction and hence low catalytic activity. It is proposed that methanol is protonated on catalysts surface by the labile H+ due to N-H bond scission. Co-adsorption of acidity probes with aniline and methanol indicates that aniline methylation takes place at single acid-base site. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Aniline; Cu1-xZnxFe2O4; desorption limited; DRIFT; IR; Methanol; N-methylaniline; N-methylation; reaction mechanism

Adsorption of methanol on Si(100)/SiO(2)and mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Ravi, V.; Jacob, Nalini E.; Patil, K. R. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
Adsorption of methanol on SiO(100)/SiO2 substrate and mesoporous SBA-15 has been studied by using Fourier transform infrared (FTIR) and X-ray photoelectron spectroscopy (XPS). Contact angle technique is employed to study the adsorption kinetics of methanol on SiO(100)/SiO2 and thermal stability of adlayer. Thermogravimetric (TGA) technique is used to understand the thermal behavior of methanol layer on SBA-15. Adsorption kinetics fit fairly well with Langmuir isotherms giving adsorption rate constant, k(a) = 0.0021 W s(-1). FTIR results show formation of methoxy silicon (SiOCHA silicon polyhydride (SiH2), carboxylate, molecular water and hydroxyl groups on Si(100)/SiO2 surface and only methoxy silicon on SBA-15. XPS results confirm methanol adsorption and support FTIR results. The methanol adlayers are found to be thermally stable up to a temperature of similar to 262 degrees C on both Si(100)/SiO2 and SBA-15 and decompose between 262 and 450 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; desorption; kinetics; Methanol; SBA-15; Si(100)/SiO2; thermal stability

Nature and mode of addition of phosphate precursor in the synthesis of aluminum phosphate and its influence on methanol dehydration to dimethyl ether - Kumar, V. Siva; Padmasri, A. H.; Satyanarayana, C. V. V.; Reddy, I. Ajit Kumar; Raju, B. David; Rao, K. S. Rama (Catalysis Communications, 2006)
Four aluminum phosphate catalysts with Al/P = 1 were prepared by precipitation of mixture of aluminum nitrate and phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate) with NH3 and precipitation of aluminum nitrate with NH3 followed by impregnation of phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate). The catalysts were characterized, using different physico-chemical methods viz., BET-S.A., XRD, FT-IR, and NH3-TPD. Al-27 and P-31 MAS NMR spectroscopy was used to characterize selected catalysts in order to find out the presence of Al and P environments. The catalytic conversion of methanol to dimethyl ether was conducted over these catalysts in a temperature range of 448-548 K at atmospheric pressure. AIPO(4) prepared by precipitating the mixture of aluminum nitrate and (NH4)(2)HPO4 with aq. NH3 generated more number of moderate acid sites and showed higher methanol dehydration activity with 100% selectivity to DME at 548 K. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Al-27 and P-31 MAS NMR; aluminum phosphate; dehydration; dimethyl ether; Methanol; NH3-TPD

Adsorption of methanol on mesoporous SBA-15 - Mirji, S. A.; Halligudi, Shivaraj B.; Mathew, Nevin T.; Jacob, Nalini E.; Patil, K. R.; Gaikwad, A. B. (Materials Letter, 2007)
The adsorption of methanol onmesoporous SBA-15 has been studiedbyrising Brunauer-Emmett-Teller (BET) surface area analysis, scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, X-ray photoclectrom spectroscopy (XPS) and tbennogravimettic analysis (TGA). The BET surface area analysis shows decreases of the surface area from 387 to 383 m(2)/g, pore volume from 0.88 to 0.81 cm(3)/g and pore diameter from 9.07 to 8.4 mm after methanol adsorption. The appearance of strong IR bands at 2862 and 2964cm(-1) due to methyl (-CH3) symmetric and asymmetric stretching demonstrate the presence of methanol and evidence of successful methanol adsorption. XPS results show increase of carbon and oxygen content on the surface of SBA-15. Thermogravirriettic analysis shows that the methanol adsorbed on SBA-15 is stable up to a temperature of 265 degrees C and that the methanol adlayers decompose between 265 and 588 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Electron microscopy; Methanol; SBA-15; Surfaces; thermal stability

Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Influence of Al3+ insertion in the stannosilicate MFI framework on the catalytic performance in vapor phase aniline N-methylation - Niphadkar, P. S.; Joshi, P. N.; Deshpande, Suvarna S.; Bokade, Vijay V. (Applied Catalysis A-General, 2011)
Silica-based Sn-MFI, Al-MFI and Al-Sn-MFI molecular sieves were synthesized by hydrothermal crystallization of gels having molar compositions SiO2:xSnO(2):yAl(2)O(3):0.23 (TPA)(2)O:35H(2)O, where x ranges from 1/0 to 1/200 and y from 1/0 to 1/400. Keeping molar Si/(Al + Sn) = 50, the amount of tin and aluminum in hydrogel was varied (Sn:Al molar ratios = 1:0, 1:0.33, 1:1, 1:3, 0:1) to investigate the synergy between Lewis and Bronsted acid sites in acid catalyzed aniline N-methylation reaction. Catalyst characterization was done by Powder X-ray diffraction, DRUV-vis spectroscopy, temperature programmed ammonia desorption (TPAD) and FTIR spectroscopy. An increase in the Al3+ insertion in Sn-MFI framework resulted in the increase in the stronger acid sites. Al-Sn-MFI showed higher aniline conversion than their monometallic counterparts. A sample having B/L ratio in between 0.67 and 0.91 was found to be optimum for maximizing the NMA yield, indicating the existence synergistic properties of Al-Sn-MFI. Upon process parameter optimization, the optimum sample M50 [Si/Al = 50.2, Si/Sn = 93.8, Si/(Al + Sn) = 43.2] showed the maximum aniline conversion (67%) and NMA selectivity (81%) at reaction temperature = 220 degrees C, weight hourly space velocity (WHSV) = 3 h(-1), molar ratio (aniline to methanol) = 1:8 and TOS = 4 h. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Al-Sn-MFI; Aniline; Bronsted and Lewis acid; Methanol; N-methylaniline

Structure-tailored surface oxide on Cu-Ga intermetallics enhances CO2 reduction selectivity to methanol at ultralow potential - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C. (Advanced Materials, 2022)
Electrochemical CO2 reduction reaction (eCO(2)RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of -0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO(2)RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2O3, which is probed by in situ XAFS, quasi in situ powder X-ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope-labeling experiments in presence of (CO2)-C-13. Finally, to minimize the mass transport limitations and improve the overall eCO(2)RR performance, a poly(tetrafluoroethylene)-based gas diffusion electrode is used in the flow cell configuration.
Keywords: (2) reduction; CO; Electrochemistry; Methanol

Comprehensive review on catalytic O-alkylation of phenol and hydroquinone - Bhongale, Priyanka; Joshi, Sunil; Mali, Nilesh (Catalysis Reviews-Science and Engineering, 2023)
The alkylation process involves two competitive paths of O- and C-alkylation and achieving better selectivity for desired products is a very challenging problem. The development of new process for synthesis of O-methylated products of phenol and dihydric phenols is a subject of high industrial and academic interest. Alkyl phenyl ethers, especially anisole and 4-methoxyphenol, have captivated significant interest due to their increasing applications in pharmaceutical industries. The main emphasis of the present review is to explore the recent development in two catalytic O-alkylation processes. The first process is O-methylation of phenol into anisole and another is selective mono O-methylation of hydroquinone into 4-methoxyphenol. The present article covers O-alkylation methods with methanol and dimethyl carbonate as alkylating agent over various acidic and basic catalytic systems. The catalyst systems analyzed involves Bronsted and Lewis acidic and basic ionic liquids, conventional acids, metal oxides, solid acid and basic catalysts, hydrotalcites, various zeolites and heteropolyacids. The mechanistic behavior of alkylation reactions in presence of different catalytic system is reviewed critically which is important to design new and/or modified catalyst in order to maximize the yield of desired product. Additionally, an influence of reaction parameters, role of catalyst and their active sites on product distribution is described. The review paper gives useful insight for researchers in the field of catalysis and reaction engineering of alkylation reactions. Understandings of the reaction pathways will help in developing reliable kinetic models necessary for process scale-up to industrial scale reactor system.
Keywords: Dimethyl carbonate; Hydroquinone; Methanol; O-alkylation; phenol

Electronic fingerprints for diverse interactions of methanol with various Zn-based systems - Mehta, Shweta; Joshi, Kavita (Surface Science, 2023)
We have investigated various Zn-based catalysts for their interaction with methanol (MeOH). MeOH is one of the most critical molecules being studied extensively, and Zn-based catalysts are widely used in many industrially relevant reactions involving MeOH. We note that the same element (Zn and O, in the present study) exhibits different catalytic activity in different environments. The changing environment is captured in the underlying electronic structure of the catalysts. In the present work, we compared the electronic structure of Zn-based systems, i.e., ZnAl2O4 and ZnO along with oxygen preadsorbed Zn (O-Zn) and metallic Zn. We demonstrate the one-to-one correlation between the pDOS of the bare facet and the outcome of that facet's interaction (i.e. either adsorption or dissociation of MeOH) with MeOH. These findings would pave the way towards the in-silico design of catalysts.
Keywords: DFT; Electronic properties; Methanol; Zn-based systems; ZnO

Mechanistic insights into near ambient pressure activity of intermetallic NiZn/TiO2 catalyst for CO2 conversion to methanol - Dongapure, Pavan; Tekawadia, Jyoti; Thundiyil, Shibin; Caha, Ihsan; Deepak, Francis Leonard; Devi, R. Nandini (ChemCatChem, 2023)
Ni-Zn pair is predicted through descriptor-based studies to be conducive for CO2 hydrogenation. In this study, NiZn (1 : 1) intermetallics supported on TiO2 is identified as a potential candidate for near ambient pressure activity. The effect of reduction temperature on the catalyst textural properties as well as on CO2 to methanol reduction are explored. Structural and microscopic studies provide clear evidence of phase evolution of NiZn alloy with increasing reduction temperatures, along with phase variations of Zn based oxides. Interface between NiZn intermetallics and ZnO nanoparticles observed at reduction temperature of 550 degrees C, seems to play a crucial role in making this system most active and selective to methanol. In addition, in-situ IR studies provide mechanistic insights and indicates the formation of methanolic species even at ambient pressure.
Keywords: CCUS; CO2; In-situ IR; Methanol; near ambient pressure

Experimental and kinetic modelling studies for the design of fixed bed methanol reactor over CuZA catalyst - Bagwan, Farahanaz M.; Dongapure, Pavan; Kulkarni, Amol A.; Vasireddy, Satyam Naidu (Chemical Engineering Research Design, 2024)
Direct conversion of CO 2 via hydrogenation to value-added chemicals is a vital approach for utilising CO 2 emitted into the atmosphere. In this paper, a critical analysis of reaction kinetic modelling studies is explored in a fixed bed reactor to improve methanol yield for different H 2 to CO 2 ratios by simulating a lab-scale reactor for adiabatic and isothermal conditions. The feed inlet temperature and pressure variations are applied to study the effect of both configurations on methanol production. The results show that the isothermal configuration yields 2.76% more methanol yield compared to the adiabatic reactor. The effect of H 2 to CO 2 molar ratios of 3, 6 and 9 on the performance of the catalyst and the influence of CO and CO 2 hydrogenation is investigated with model simulations. The overall methanol yield is increased from 19.03% to 36.41% with increase in H 2 to CO 2 molar ratio from 3 to 9. Experiments are performed using commercial copper-based catalyst for different temperatures of 210, 230 and 250 degrees C at a pressure of 40 bar for H 2 /CO 2 of 3 and GHSV of 720 h -1 as well as at optimal temperature of 250 degrees C and 50 bar with varying H 2 /CO 2 of 3, 6, 9 for 3 g and 6 g catalyst. The maximum methanol yield of 2.53% and space time yield of 13.59 mg/g cat .h is obtained at H 2 /CO 2 ratio of 9.
Keywords: CO2 conversion; CuZA catalyst; H2 toCO2 molar ratio; Kinetic modelling; Methanol

Deciphering the intricate mechanisms behind the selective oxidation of methane to C1 and C2 oxygenates over FeAu/γ-Al2O3 catalysts - Prabu, Marimuthu; Manikandan, Marimuthu; Rengam, B. Sathya Sai; Ramakrishnan, Archana; Raja, Abhishekram; Urkude, Rajashri R.; Ghosh, Biplab; Varghese, Jithin John; Raja, Thirumalaiswamy (Chemical Engineering Journal, 2025)
In this work, we demonstrate an eco-benign synthesis protocol for preparing gold nanoparticles and the role of the strong interaction between gold nanoparticles and iron oxide in FeAu/gamma-Al2O3 catalysts that render it an anionic (Au delta-) character while tailoring them in a smaller size. The multifunctional FeAu/gamma-Al2O3 catalyst selectively produces ethanol (95 % selectivity, similar to 240 mu mol(-1) cat) at a mild temperature of 75 degrees C without the addition of co-reactants during liquid phase methane oxidation with molecular oxygen. Conversely, Au/gamma-Al2O3 and Fe/gamma-Al2O3 catalysts exhibited high selectivity for CH3OH and HCHO. A high dispersion accompanied by strong electronic interaction between the Au delta–FeOx, as corroborated by diverse techniques, enables methane activation across the interface and coupling on the gold nanoparticles, which are responsible for the markedly improved formation of ethanol. Furthermore, in situ DRIFTS studies and DFT investigations point to a reaction mechanism of coupling of CH2OH and CH3 intermediates as the most likely route for ethanol formation.
Keywords: Anionic gold catalysts; Au-FeOx synergism; C-H bond activation; Ethanol; Methane oxidation; Methanol